Cost asymmetry in the Italian Mutual Banks and comparison among Less Significant Banks - Piatti, Domenico; Cincinelli, Peter; Cattaneo, Cristiana; Bassani, Gaia (European Scientific Journal, ESJ, 2024)
In this paper, we study the cost asymmetry in the Italian banking system. The analysis is conducted on a sample of Italian Less Significant Banks (including Mutual banks) during 2006-2019 time period. We find that asymmetric behavior in total costs, among Less Significant Banks, is higher in Mutual ones, and that the asymmetry in total costs significantly varies with different levels of credit risk. We also find that more efficient banks, whether Mutual Banks or not, mitigate total cost asymmetry.